A study on management of maternal anemia with infusion of intravenous iron sucrose and its outcome in management of anemia - R., Uma Maheswari; Veerakumaran, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In India, women become pregnant with low baseline hemoglobin level resulting in high incidence of moderate to severe anemia in pregnancy where oral iron therapy cannot meet the requirement. Pregnant women with moderate anemia are to be treated with parenteral iron therapy. The aim of the study is to the infusion of intravenous iron sucrose and its outcome in the management of anemia. Methods: Totally 100 pregnant females were included in the study. The study period was from January 2018-July 2018 at vanavil medical center in Chennai. 50 Patients of Group A was given oral iron tablets containing100mg of elemental iron. 50 patients of Group B was given a total of 1000 mg of intravenous iron sucrose divided into five doses of 200 mg each at weekly intervals. Estimation of hemoglobin was started 4 weeks after commencement of iron therapy and then repeated every 4 weeks till 36 weeks of gestation, pre-delivery and postpartum. Results: Target hemoglobin levels were achieved in 4 weeks’ time in 19 (76%) patients in the iron sucrose group as compared to 08 (32%) of patients in the oral iron group. There was a significant improvement in the various hematological parameters in iv sucrose group as compared to patients in the oral iron group. There were no significant allergic reactions in iv sucrose group. Conclusions: Our results showed that intravenous iron sucrose therapy was effective to treat moderate anemia in pregnant women. Intramuscular preparations are known to be associated with local side-effects. Iron sucrose complex iv therapy was with negligible side effects. It caused a rapid rise in hemoglobin level and the replacement of stores was faster. Long term comparative studies are required to assess if they can be used at a peripheral level.